2003
DOI: 10.1021/ja034468o
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Investigation of the Carbon−Carbon Bond Cleavage of Aryl and Alkyl Cyanides Using a Cationic Rh(III) Silyl Complex

Abstract: Cationic Rh(III) complex [Cp(PMe(3))Rh(SiPh(3))(CH(2)Cl(2))]BAr(4)' (1) activates the carbon-carbon bond of aryl and alkyl cyanides (R-CN, where R = Ph, (4-(CF(3))C(6)H(4)), (4-(OMe)C(6)H(4)), Me, (i)Pr, (t)Bu) to produce complexes of the general formula [Cp*(PMe(3))Rh(R)(CNSiPh(3))]BAr(4)'. With the exception of the (t)BuCN case, every reaction proceeds at room temperature (t(1/2) < 1 h for aryl cyanides, t(1/2) < 14 h for alkyl cyanides). A general mechanism is presented on the basis of (1) an X-ray crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 14 publications
5
75
0
2
Order By: Relevance
“…Similar silyl-assisted nitrile C-C bond cleavage was reported independently by Bergman, Brookhart and co-workers using Rh [22] and Ir [23] complexes. Later, Hashimoto et al [24] and Tobiso et al [25] and their co-workers reported this type of silyl-assisted nitrile C-C bond cleavage.…”
Section: Stoichiometric C-cn Bond Cleavage Of Acetonitrile By a Silylsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar silyl-assisted nitrile C-C bond cleavage was reported independently by Bergman, Brookhart and co-workers using Rh [22] and Ir [23] complexes. Later, Hashimoto et al [24] and Tobiso et al [25] and their co-workers reported this type of silyl-assisted nitrile C-C bond cleavage.…”
Section: Stoichiometric C-cn Bond Cleavage Of Acetonitrile By a Silylsupporting
confidence: 83%
“…Thus the reaction on changing the molar ratio of Et 3 SiH and MeCN was examined. Reaction of Et 3 SiH with a 10-fold molar excess of MeCN in the presence of 0.83 mol% CpFe(CO) 2 [22] systems, this catalytic system is very effective.…”
Section: Consideration Of Catalytic Cyclementioning
confidence: 99%
“…Jesson and coworkers (21) have also documented the formation of the cyanomethyl hydride as a result of activation of acetonitrile using (dmpe) 2 M(Np)H (M ϭ Fe, Ru; Np ϭ 2-naphthyl). The scission of the COCN bond of acetonitrile has also been reported by Parkin and coworkers (22), Brookhart and coworkers (23,24), Nakazawa et al (25), and Jones and coworkers (26). Of particular interest is the work by Brookhart using a similar Cp*Rh(PMe 3 ) system (23), which is known to undergo COH bond activation in the presence of alkanes and arenes (3,27).…”
mentioning
confidence: 57%
“…Examples of such g 1 -bound aryl complexes are relatively less common in the literature [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. It may be added in this context that metal mediated C-N bond cleavage, though not very uncommon, is mostly limited to strained amines and amidines [74][75][76][77][78][79], and hence there is significant interest in transition metal mediated C-N bond cleavage [80][81][82][83][84][85][86][87][88][89].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%